Congitive conflict mahasiswa pada penyelesaian masalah matematika - Sutopo Sutopo (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2021)
In solving math problems, cognitive conflict can take many forms, for example: when students' expectations are proven wrong when solving a problem; and arise as a result of educators or other students expressing opposing opinions. The research aims to: 1) Describe student errors when solving math problems, and 2) To describe students' cognitive conflicts in solving mathematical problems. This research is a qualitative research with a case study research strategy. The subjects of this study were fourth semester students of mathematics tadris IAIN Tulungagung. The research instrument consisted of test questions and interview guidelines. Subjects were asked to work on problems individually and based on their work, then an interview was conducted to determine their thought processes and cognitive conflicts. The results of this study indicate that: 1) Student errors when solving math problems, especially integrals, include: students do not understand the use of the symmetry theorem, and the use of types of functions, 2) Cognitive conflicts that occur in mathematics tadris students of IAIN Tulungagung in solving math problems include; a) conflict between conception and conception. When the subject sees that the final result is not the same, the cognitive conflict situation experienced will encourage their cognitive ability to seek justification, confirmation or verification of their opinion. b) conflict between conception and outcome. The subject uses his conception by producing an area value that is not in accordance with his expectations, including area values that are negative and zero.